Social research from educational practice in the escuela militar of suboficiales sargento Inocencio Chíncá (Quaestiones Disputatae: temas en debate, 2021)
This academic article arises from an analysis of the teaching and educational practice with the students of the Escuela Militar de Suboficiales "Sargento Inocencio Chincá”, from which it is intended to communicate the social research processes that are presented in the classroom, through the proposals of degree work of the students and the knowledge (subjects) that teachers develop to guide the training process, studying reality as a social phenomenon from the context in which they are located and taking into account the multiculturalism that occurs in the students, generating the formulation and design of research proposals that strengthen the to training actors who contribute and intervene in the social, environmental andcultural transformation of the national territory.
Keywords: Education; Military Context; Social Research; Educational Practice